From first symptoms to final diagnosis of Cushing's disease: experiences of 176 patients - Kreitschmann-Andermahr, Ilonka; Psaras, Tsambika; Tsiogka, Maria; Starz, Daniel; Kleist, Bernadette; Siegel, Sonja; Milian, Monika; Kohlmann, Johannes; Menzel, Christa; Fuehrer-Sakel, Dagmar; Honegger, Juergen; Sure, Ulrich; et al. (European Journal of Endocrinology, 2015)
To obtain structured information on the diagnostic delay in patients with Cushing's disease (CD) from the patients perspective to provide leverage points for earlier diagnosis.The study includes 176 patients with ACTH-dependent CD who had received pituitary surgery completed a self-developed questionnaire on their symptomatology before the illness was diagnosed, the course and length of the diagnostic process, and the role of the involved health care professionals.Data were analyzed statistically. Answers in free text options were categorized and counted.The overall diagnostic process took 3.8±4.8 years (median 2 years), during which 4.6±3.8 (1-30) physicians were consulted, most frequently the family physician (FP; 83.0%). The presented symptoms were various and often vague, e.g. 'poor general condition' (at FPs), or very common in the field of the visited specialist (i.e. 'skin changes' at dermatologists). Women recognized the first CD symptoms themselves significantly more frequently than men, whereas physicians recognized CD symptoms significantly more frequently in males.A clear difficulty of diagnosing CD seems that patients describe isolated symptoms to the FP or the respective specialists according to their fields of specialization. As FPs are contacted most frequently, they should be trained to recognize the broad spectrum of CD symptoms, especially in female patients with weight gain, and initiate endocrinological referral.
EVALuna2:22869